A visitor that has come to stay? The case of pink salmon (Oncorhynchus gorbuscha) in Norway - Aspelund, Andrea Sofie Hansen (UiT The Arctic University of Norway, 2020)
This thesis is dedicated to the case of the pink salmon (Oncorhynchus gorbuscha) in Norway. The pink salmon has a large native range and is indigenous to regions of the Pacific Ocean. It was deliberately introduced into rivers that drained into the White Sea by the Soviet Union. This was done through several attempts reaching from 1957 to 2001. These attempts resulted in secondary expansion to the Northern Atlantic and the Barents Sea. The pink salmon demonstrated a high ability to disperse but did not show signs of establishment. Low amount of pink salmon has been observed in the following decades after the attempts of introduction. This remained the case until a sudden and rapid change in 2017. In 2017, pink salmon were observed and caught in over 200 rivers in Norway. Several other countries in northern Europe also experienced an increase in the abundance of spawning pink salmon, but Norway had the highest increase. The pink salmon has distinct groups of odd year- and even year broodlines. The odd year broodline appears to be the strongest, which is further supported by the high amount of pink salmon in 2019. Alien species are considered as the second biggest threat to biological diversity by the Norwegian government (regjeringen.no). Alien species are to be managed in accordance with national legislation and international agreements. The thesis aim is to ascertain whether the pink salmon has come to Norway to stay based on the properties of the management system and the unique biological characteristics of the pink salmon. Challenges are identified and assessed by acquiring an overview of the management system and the pink salmon itself. This thesis has a multidisciplinary approach, because there are several aspects of the case that can determine the outcome. Keywords: Alien species, Alien invasive species, Norwegian management system, risk management, implementation theory, conservation biology